2019
DOI: 10.17323/727-0634-2019-17-1-89-102
|View full text |Cite
|
Sign up to set email alerts
|

Changing Fertility Patterns in Two North Caucasian Republics: Is it Only Social Policy that Matters?.

Abstract: The paper deals with fertility levels in some republics of the North Caucasus (Dagestan and Karachay-Cherkessia) where, as in other post-Soviet regions, there has been a serious intensification of religiosity and at the same time weakening of the traditional family unit in recent decades. The goal of the paper is to ascertain whether these trends affect fertility, whose decrease is apparently stalling in the North Caucasus over the last decade. One reason to turn to this question is that in some regions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Among them, although concerned with the fertility trends after the demise of the Soviet regime only, Kozlov (2019) showed that in the regions of the Russian North Caucasus, where Muslims were the majority of the population, the religiosity of respondents was related to higher fertility, regardless of family policy issues. This seems to suggest that an Islamic revival within a given society can support fertility.…”
Section: Gender Role Beliefs and Fertilitymentioning
confidence: 99%
“…Among them, although concerned with the fertility trends after the demise of the Soviet regime only, Kozlov (2019) showed that in the regions of the Russian North Caucasus, where Muslims were the majority of the population, the religiosity of respondents was related to higher fertility, regardless of family policy issues. This seems to suggest that an Islamic revival within a given society can support fertility.…”
Section: Gender Role Beliefs and Fertilitymentioning
confidence: 99%